An advanced electrocatalyst with exceptional eletrocatalytic activity via ultrafine Pt-based trimetallic nanoparticles on pristine graphene. (June 2015) - Zhao, Jian; Li, Hongqi; Liu, Zhensheng; Hu, Wenbin; Zhao, Changzhi; Shi, Donglu
Abstract: It has been a great challenge to directly deposit uniform metal particles onto pristine graphene due to its low surface energy and chemical inertness. Without any surfactant or functionalization, we have developed a unique synthesis of high-quality PtRuNi trimetallic nanoparticles supported on pristine graphene via a simple but effective supercritical route. Due to excellent wettability between supercritical carbon dioxide and the carbon surface, ultrafine metal particles are uniformly and firmly anchored on the graphene sheets. While well retaining its intrinsic structure and outstanding electronic conductivity, the pristine graphene with well-dispersed PtRuNi trimetallic nanoparticles shows significantly improved catalytic activity towards methanol oxidation, which is at least ten times higher than those of the commercial Pt/C and homemade Pt/XC-72 catalysts. The resulting trimetallic hybrid also exhibits high stability as compared to Pt and PtRu/pristine graphene composites and the reduced graphene oxide counterparts. In principle, the supercritical method can be applied to other metal nanoparticles in fabrication of high-performance graphene-based nano-catalysts.